Dynamic Transitions in Fish Community Composition From the Amazon River Plume to Offshore Reefs - Osmar J. Luiz; Bruno E. Soares; Lucas T. Nunes; Israel Hidenburgo Cintra; Ronaldo Borges Barthem; Alexandre P. Marceniuk (Journal of Biogeography, 2026)
Aim To investigate the spatial and temporal dynamics of fish assemblages across the Northern Brazilian Shelf, a vast and complex ecosystem influenced by the Amazon River plume, we aimed to identify fish assemblage types, understand transitions between them from the river mouth to offshore reefs, and examine seasonal changes related to plume dynamics. Location Northern Brazilian Shelf (Western Atlantic Ocean), from the Amazon River mouth to the Great Amazon Reef System (GARS). Taxon Actinopterygii and Elasmobranchii. Methods We applied a presence‐absence Latent Dirichlet Allocation (LDA) model to fish occurrence records. This Bayesian mixed‐membership probabilistic approach inferred latent assemblages by analysing co‐occurring species and quantifying community types at the same site in varying proportions, suitable for characterising transitions. We then mapped these assemblages' proportional contributions and analysed their spatial distribution relative to seasonal changes in river discharge and freshwater plume influence. Results Four fish assemblages were identified with a clear coast‐to‐offshore zonation: (1) freshwater‐tolerant plume assemblage near the river mouth; (2) an estuarine–mud–plain assemblage on the inner shelf; (3) a mixed‐sand corridor assemblage in mid‐shelf; and (4) a reef‐associated assemblage on outer‐shelf GARS. The first three assemblages showed a seasonal reorganisation. During the wet season, strong plume influence led to spatially segregated assemblages. Conversely, the dry season's reduced plume resulted in increased community overlap, centred on the mid‐shelf assemblage. The reef assemblage (4) remained spatially stable across seasons. Main Conclusions The Amazon River plume's seasonal dynamics primarily drive fish community structure and connectivity across the Northern Brazilian Shelf. This study uncovers how assemblages transition from being shaped by environmental filtering (exhibiting strong zonation during peak plume) to a more overlapping distribution as plume influence weakens. These findings underscore the need for dynamic, seasonally adjusted management to conserve biodiversity and ecosystem function in this significant, and increasingly threatened, estuarine–marine transition zone.

Marine teleost fishes of the northeastern Brazilian coast: 166 years of compiled data - Ricardo S. Rosa; Aline P. M. Medeiros; Antônio Felinto; Camila Brito; Erika F. C. Santana; Fernanda V. Albuquerque; Jonas A. Santos; Júlio Lustosa; Katherine M. P. Viana; Marianna B. Silva; Rafael Menezes; Viviana Márquez Velásquez; et al. (Systematics and Biodiversity, 2023)

The marine catfishes of the genus Bagre (Siluriformes; Ariidae) from the Western Atlantic - Alexandre P. Marceniuk; Claudio Oliveira; João Bráullio L. Sales; Ricardo Betancur-R (Marine Biodiversity, 2022)

Multiple lionfish (Pterois spp.) new occurrences along the Brazilian coast confirm the invasion pathway into the Southwestern Atlantic - Osmar J. Luiz; Wagner C. R. dos Santos; Alexandre P. Marceniuk; Luiz A. Rocha; Sergio R. Floeter; Clara E. Buck; Alex G. C. M. de Klautau; Carlos E. L. Ferreira (Biological Invasions, 2021)

Redescription of the blacktip sea catfish Plicofollis dussumieri (Valenciennes) (Siluriformes: Ariidae), with a new record from the Red Sea and notes on the diversity and distribution of Plicofollis spp. - Alexandre P. Marceniuk; Sergey V. Bogorodsky; Ahmad O. Mal; Tilman J. Alpermann (Marine Biodiversity, 2017)

Redescription of Notarius grandicassis and Notarius parmocassis (Siluriformes; Ariidae), with insights into morphological plasticity and evidence of incipient speciation - Alexandre P. Marceniuk; Raquel Siccha-Ramirez; Ronaldo Borges Barthem; Wolmar Benjamin Wosiacki (Systematics and Biodiversity, 2017)

Apparent signal of competition limiting diversification after ecological transitions from marine to freshwater habitats - Ricardo Betancur‐R.; Guillermo Ortí; Ariel M. Stein; Alexandre P. Marceniuk; R. Alexander Pyron (Ecology Letters, 2012)
Adaptive radiations are typically triggered when a lineage encounters a significant range of open niche space (ecological opportunity), stemming from colonisation of new areas, extinction of competitors or key innovations. The most well‐known of these is the colonisation of new areas, through either dispersal into new regions or the invasion of novel ecological regimes. One aspect of ecological opportunity that has rarely been studied, however, is the extent to which pre‐existent competitors act to limit diversification in newly colonised adaptive zones. Herein, we show that in multiple geographically independent invasions of freshwaters by marine Sea Catfishes (Ariidae), rates of both morphological disparification and lineage diversification are inversely related to the presence and diversity of other freshwater fish lineages. Only in one region (Australia‐New Guinea) with an otherwise depauperate freshwater fauna, has an ariid invasion gained any substantial traction. This is true at both regional and community scales, suggesting that competitive constraints may be an important factor regulating adaptive radiation.